PENGARUH INDEPENDENSI AUDITOR DAN TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT - Maria Yonitha Manbait; Suryaningsi (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2020)
This study aims to determine the effect of auditor independence and time budget pressure on the quality of audiences, either partially or simultaneously. Population is the auditor BPK RI Representative of NTT Province in Kupang City. The data collection technique used a questionnaire. The sampling technique uses the Census Technique. The number of samples collected was 35. The results showed that auditor independence had a positive effect on audit quality, indicated by the regression coefficient value of 0.556 and the t value of 8.350> t table 2.03693 and the sig level of 0.000 <0.05, which means that independence has an effect on audit quality. Time budget pressure has an effect but is negative on audit quality, indicated by the regression coefficient value of -0.133, and the t value of -2.237 <t table 2.03693 and the sig level of 0.032> 0.05, which means that the lower the Time Budget Pressure, the resulting audit quality more increasing. Simultaneously independence and time budget pressure have an effect on audit quality as indicated by the value of f count 37.328> f table 3.29 and a sig level of 0.000 <0.05.